2022
DOI: 10.7554/elife.80550
|View full text |Cite
|
Sign up to set email alerts
|

Retinopathy of prematurity: Metabolic risk factors

Abstract: At preterm birth, the retina is incompletely vascularized. Retinopathy of prematurity (ROP) is initiated by the postnatal suppression of physiological retinal vascular development that would normally occur in utero. As the neural retina slowly matures, increasing metabolic demand including in the peripheral avascular retina, leads to signals for compensatory but pathological neovascularization. Currently, only late neovascular ROP is treated. ROP could be prevented by promoting normal vascular growth. Early pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 220 publications
0
8
0
Order By: Relevance
“…Regarding the inflammatory markers selected for this study, IL-6 was chosen for its well-established role as a primary pro-inflammatory cytokine and its recognized association with neonatal complications, such as sepsis, necrotizing enterocolitis, and even ROP [ 9 , 51 ]. Similarly, CRP, an acute-phase reactant that rises rapidly during inflammation and infection, was selected for its routine use in monitoring these conditions and its proposed relationship with ROP development [ 17 , 51 ]. The combined assessment of these two markers allows for a more comprehensive understanding of the neonates’ inflammatory status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the inflammatory markers selected for this study, IL-6 was chosen for its well-established role as a primary pro-inflammatory cytokine and its recognized association with neonatal complications, such as sepsis, necrotizing enterocolitis, and even ROP [ 9 , 51 ]. Similarly, CRP, an acute-phase reactant that rises rapidly during inflammation and infection, was selected for its routine use in monitoring these conditions and its proposed relationship with ROP development [ 17 , 51 ]. The combined assessment of these two markers allows for a more comprehensive understanding of the neonates’ inflammatory status.…”
Section: Discussionmentioning
confidence: 99%
“…Extremely premature and very premature neonates are known to be at a higher risk of developing ROP due to their underdeveloped retinal vasculature and their increased susceptibility to oxidative stress and inflammation [ 14 ]. In these infants, the immature immune system and exposure to various stressors, such as infections and mechanical ventilation, can result in a heightened inflammatory response, further contributing to the development and progression of ROP [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…This condition is often complicated by oxygen therapy for respiratory diseases [ 77 ]. Recent studies have identified metabolic abnormalities in the occurrence and progression of ROP [ 78 ]. Despite the existence of many mitochondria, photoreceptors, which are a crucial component of the outer retina, primarily rely on aerobic glycolysis rather than OXPHOS for metabolism.…”
Section: Metabolic Reprogramming In Neonatal Hyperoxia-associated Dis...mentioning
confidence: 99%
“…Mechanisms behind delayed physiological retinal vascularization are not fully understood. It is well established that hyperoxia causes suppression of physiological retinal vascular growth [ 5 ]. However, there is another very important factor contributing to suppression of physiological retinal vascular growth.…”
Section: Introductionmentioning
confidence: 99%